2006
DOI: 10.1111/j.1365-2958.2006.05061.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct repeat‐mediated deletion of a type IV pilin gene results in major virulence attenuation of Francisella tularensis

Abstract: SummaryFrancisella tularensis , the causative agent of tularaemia, is a highly infectious and virulent intracellular pathogen. There are two main human pathogenic subspecies, Francisella tularensis ssp. tularensis (type A), and Francisella tularensis ssp. holarctica (type B). So far, knowledge regarding key virulence determinants is limited but it is clear that intracellular survival and multiplication is one major virulence strategy of Francisella . In addition, genome sequencing has revealed the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(147 citation statements)
references
References 57 publications
4
142
1
Order By: Relevance
“…F. tularensis subsp. holarctica deleted for the pilE1 (pilA) gene is severely attenuated for virulence in mice when administered by the subcutaneous route, but only slightly defective for intramacrophage replication (Forslund et al, 2006). A deletion in pilE1 is also present in the LVS, and the authors of that study suggested that the LVS pilE1 mutation may be responsible, at least in part, for the attenuation of LVS.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…F. tularensis subsp. holarctica deleted for the pilE1 (pilA) gene is severely attenuated for virulence in mice when administered by the subcutaneous route, but only slightly defective for intramacrophage replication (Forslund et al, 2006). A deletion in pilE1 is also present in the LVS, and the authors of that study suggested that the LVS pilE1 mutation may be responsible, at least in part, for the attenuation of LVS.…”
Section: Introductionmentioning
confidence: 79%
“…These results are consistent with the reported attenuation in intramacrophage growth seen with an F. tularensis subsp. holarctica pilE1 mutant (Forslund et al, 2006). These results demonstrate that PilE1 and protein secretion, but not Tfp biogenesis, contribute to intramacrophage growth in vitro.…”
Section: Tfp/protein Secretion Functional Overlapmentioning
confidence: 99%
“…We have seen similar effects in other studies where we examined the role of a pilin gene, pilA, in virulence. In one study, where we used a moderately virulent strain isolated from a hare, we found that PilA mutants were severely attenuated compared to a strain expressing PilA (16). In contrast, when pilA mutants of virulent strains like FSC200 and the type A strain Schu S4 were used to infect mice, the level of attenuation was lower (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…The genes required for the production of type IV pili exist in Francisella, and ultrastructural analysis of the LVS revealed the presence of long protrusions with the appearance of type IV pili [12]. Deletion of one of the putative pilin genes in a type B strain of F. tularensis results in attenuation of virulence [13], further implicating type IV pili in the pathogenesis of tularemia. Finally, deletion of the tolC or ftlC genes in the LVS decreases the resistance of the organism to anti-bacterial agents, and, in the case of the former, causes attenuation of virulence in mice [14].…”
Section: Introductionmentioning
confidence: 99%